Sentence Comprehension in Primary Progressive Aphasia: A Study of the Application of the Brazilian Version of the Test for the Reception of Grammar (TROG2-Br) - Carthery-Goulart, Maria Teresa; de Oliveira, Rosimeire; de Almeida, Isabel Junqueira; Campanha, Aline; da Silva Souza, Dayse; Zana, Yossi; Caramelli, Paulo; Machado, Thais Helena (Frontiers in Neurology, 2022)
Sentence comprehension deficits have been described in patients with Primary Progressive Aphasia (PPA). However, most instruments to address this domain in more detail and in a clinical context have not been adapted and translated into several languages, posing limitations to clinical practice and cross-language research. Objectives: (1) to test the applicability of the Brazilian version of the Test for Reception of Grammar (TROG2-Br) to detect morphosyntactic deficits in patients with PPA; (2) to investigate the association between performance in the test and sociodemographic and clinical variables (age, years of formal education, disease duration); (3) to characterize the performance of individuals diagnosed with PPA (non-fluent, semantic and logopenic) and mixed PPA (PPA-Mx) and analyze whether TROG-2 may assist in the distinction of these clinical profiles. Methods: 74 cognitively healthy participants and 34 individuals diagnosed with PPA were assessed with TROG2-Br. Overall scores (correct items, passed blocks), types and categories of errors were analyzed. Results: In controls, block scores were correlated with years of formal education (Spearman r=.33, p=.004) but not with age. In PPA, age, education and disease duration were not associated with performance in the test. Controls presented higher performance on TROG2-Br compared to PPA individuals and their errors pattern pointed to mild general cognitive processing difficulties (attention, working memory). PPA subtypes did not present significant differences in the number of passed blocks or number of correct items on TROG2-Br. Error type analysis suggested processing and morphosyntactic deficits in PPA-NF/A, PPA-L and PPA-Mx. PPA-S subgroup was qualitatively more similar to controls (processing difficulties and lower percentage of morphosyntactic errors). TROG2-Br presented good internal consistency and concurrent validity. Discussion: These results corroborate findings with TROG-2 in other populations. The performance of typical older adults with heterogeneous levels of education is discussed along with recommendations for clinical use of the test and future directions of research.